2014
DOI: 10.1161/hypertensionaha.114.04262
|View full text |Cite
|
Sign up to set email alerts
|

Home Blood Pressure and Cardiovascular Outcomes in Patients During Antihypertensive Therapy

Abstract: Cardiovascular events tend to occur in the morning, along with a peak in ambulatory BP, 6 and of clinic, 24-hour, awake, sleep, evening, preawake, and morning BP, morning systolic BP (SBP) is the strongest independent predictor for stroke. Therefore, antihypertensive treatment for morning hypertension is likely to offer greater benefit in preventing cardiovascular events.Abstract-This study aimed to investigate the relationship between on-treatment morning home blood pressure (HBP) and incidence of cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 136 publications
(62 citation statements)
references
References 18 publications
5
54
1
2
Order By: Relevance
“…8,22,23 In the Home Blood Pressure Measurement With Olmesartan Naïve Patients to Establish Standard Target Blood Pressure (HONEST) study, the risk of cardiovascular events was significantly higher in patients with morning systolic BP ≥145 mm Hg and office systolic BP <130 mm Hg (hazard ratio 2.47 for cardiovascular events) than in patients with morning systolic BP <125 mm Hg and office systolic BP ≥150 mm Hg (hazard ratio 0.87). 25 The association of high systolic BP and cardiovascular risk is greatest in the morning than any other time of day, 26 and control of morning systolic BP is important for reducing cardiovascular events. Nighttime BP also has a stronger association with hypertensive target organ damage, cardiovascular events, and stroke as compared with daytime BP, 6,7,27,28 and nondipping patterns are associated with increased cardiovascular risk.…”
Section: P=0004mentioning
confidence: 99%
“…8,22,23 In the Home Blood Pressure Measurement With Olmesartan Naïve Patients to Establish Standard Target Blood Pressure (HONEST) study, the risk of cardiovascular events was significantly higher in patients with morning systolic BP ≥145 mm Hg and office systolic BP <130 mm Hg (hazard ratio 2.47 for cardiovascular events) than in patients with morning systolic BP <125 mm Hg and office systolic BP ≥150 mm Hg (hazard ratio 0.87). 25 The association of high systolic BP and cardiovascular risk is greatest in the morning than any other time of day, 26 and control of morning systolic BP is important for reducing cardiovascular events. Nighttime BP also has a stronger association with hypertensive target organ damage, cardiovascular events, and stroke as compared with daytime BP, 6,7,27,28 and nondipping patterns are associated with increased cardiovascular risk.…”
Section: P=0004mentioning
confidence: 99%
“…in Japan, among medicated hypertensive patients, stroke events are 3× more frequent than myocardial infarction. 17 However, in Westerners, this ratio is the opposite. the degree of MBps may partly explain this racial difference in the demographics of cardiovascular disease.…”
Section: Racial Differencementioning
confidence: 99%
“…However, morning Bp seems to be the important target of antihypertensive treatment in current clinical practice for the management of hypertension for the reasons listed in table 3. our recent large prospective observational study using home Bp monitoring demonstrated that home morning Bp during treatment is essentially a more important risk factor for cardiovascular events than clinic Bp in medicated hypertensive patients. 17 in addition, among the various phenotypes of Bp variability in sHAts, morning Bpv -including MBps defined by ABpM and home Bpv (peak home morning sBp, the standard deviation [sD] of morning sBp, and the morning-evening [Me] difference [morning sBp minus evening sBp]) defined by home Bp monitoring -is closely associated with organ damage 1,36 and the risk of cardiovascular events. 37,38 in the pAMeLA study, MBps was closely associated with nonspecific 24-hour Bpv.…”
mentioning
confidence: 99%
“…In the recent prospective HONEST study (Home Blood Pressure Measurement With Olmesartan Naive Patient, to Establish Standard Target BP), the incidence of stroke was 2.8× higher than that of myocardial infarction (2.92 versus 1.03/1000 person-years) in ontreatment hypertensive patients. 7 The slope of the association between higher BP levels and cardiovascular events has also been shown to be steeper in Asians compared with Western populations. 8 In consideration of these Asian-specific characteristics, antihypertensive medication targeting a lower systolic BP (SBP; eg, <130 mm Hg) would be of greater benefit in Asians than in Westerners, especially for reducing the risk of stroke and heart failure.…”
Section: Benefit Of Earlier Treatment Initiation Based On the 130/80 mentioning
confidence: 99%
“…These were the general population-based Ohasama Study, 32 the general practitioner-based J-HOP study (Japan Morning Surge-Home Blood Pressure), 33 a hypertensive outpatient trial on medication (HOMED-BP, Hypertension Objective Treatment Based on Measurement by Electrical Devices of Blood Pressure), 34 and the largest nationwide Japanese real-world observational study (HONEST). 7,35 Indeed, in the HONEST study, a morning home SBP of ≈125 mm Hg was associated with minimal risk for both stroke and coronary artery disease events.…”
Section: Facilitation Of a Home Bp-guided Approach In Asiamentioning
confidence: 99%